IMPLEMENTATION OF CLONIDINE AS A NEW SEDATIVE AND ANALGESIC DRUG IN THE NICU–A RETROSPECTIVE REPORT ON MEDICAL RECORDS. Issue 1 (14th December 2015) - Ragnarsson, Charlotte; Norman, Elisabeth
Abstract : Background: Adequate pain relief is crucial for neonatal intensive care. Opioids are used despite their side effects. Clonidine has been introduced to reduce the opioid doses. Clonidine has never been studied in newborn infants. This study describes the strategy and the clinical response during a three year implementation period in a Swedish level-III NICU. Methods: This is a retrospective study based on medical records, monitoring charts of physiological parameters and pain assessment, and Swedish national perinatal quality register data. Clonidine was administered to 97 patients and analyzed according to modes of intravenous administration (boluses and/or infusions). The indication, gestational and postnatal age at administration, doses, treatment duration, pain scoring, effects and concurrent medication were analyzed. Non-parametric statistics was performed (medians, IQR). Results: The infants were born at 28.6 (24.9–36.3) gestational weeks, birth weight 1058 (727–2660) g. The medication was introduced at postnatal age of 9 ((1–27) days. The maximum dosing was 1.4 microg/kg and 0.2 microg/kg/h for bolus doses and infusions, respectively, and the duration of exposure for the most common administration way (boluses followed by start of infusion) was 6 (3.8–11.5) days. The indication was sedation in 71%. Concurrent analgesics or sedatives, most commonly morphine, were given in 39% at start and 42% during the treatment period. The subjective effects were positive, and the side effects were few. Conclusions: Our study data support the benefits of clonidine with positive effects and few side effects. Pharmacokinetic and pharmacodynamics studies are needed in accordance with the FDA and EMA directives.